The street tree distribution across a streetscape reflects the social inequality of Latin American cities - Pena, João Carlos [UNESP]; Costa, Nayara Ribeiro da [UNESP]; Martello, Felipe [UNESP]; Ribeiro, Milton Cezar [UNESP] (Elsevier, 2024)
Due to the ecosystem services they provide, street trees are fundamental for the quality of life and well-being of the urban human population. However, street trees are usually not equitably distributed across streetscapes, making some demographic groups most vulnerable to the consequences of a poorly managed street tree community. In this study, we evaluated if the socioeconomic characteristics of a large Latin American metropolis (wealth and density of older adults and children) are related to aspects describing characteristics of the street tree community (number of trees, beta diversity, canopy diameter, and proportion of native trees). Our street trees database is comprised of more than 250,000 trees and 559 species. Through a model selection approach, we observed that all socioeconomic characteristics relate to an aspect of the street tree community. The number of trees increased with wealth, but the highest densities of older adults were observed in regions with fewer trees. Canopy cover, conversely, decreased in wealthier neighborhoods and in regions with a higher density of children, while increasing with the density of older adults. Beta diversity of native trees also decreased with wealth. These results not only highlight the luxury effect across the streetscape but reflect the social inequality of Latin American cities: most people from both demographic groups live in regions with a less exuberant tree cover. Our approach can help identify the strengths and weaknesses regarding the plan and management of this street tree community, assisting in the definition of public policies and guidelines for a more sustainable and equitable urban landscape.
Keywords: Beta diversity; Children; Luxury effect; Older adults; Urban forest